أثر استخدام تكنولوجيا المعلومات في تحسين جودة الخدمات في شركات الاتصالات الليبية "دراسة ميدانية علي العاملين في شركة ليبيانا للاتصالات الليبية" - د. آمال مفتاح الشاعر; أ. احلام عبد الغني العبيدي (Sharwes Scientific Journal, 2025)
The study aimed to identify the impact of using information technology in improving the quality of services in its dimensions (responsiveness, reliability, tangibility, safety, and empathy) in the Libyan Telecom Company. To obtain primary data, the researchers developed a questionnaire that was randomly distributed to a sample of the original study population. It consists of (60) questionnaires, which were collected and analyzed using the SPSS statistical package program The study reached several results, the most important of which are: an increase in the level of use of information technology and its five dimensions. It also showed an increase in the level of improvement in the quality of services. The results also showed an impact of the use of information technology represented by (responsiveness, reliability, tangibility, security, empathy) on improving the quality of services provided. In Libyana Telecommunications Company